2019
DOI: 10.1080/10550887.2019.1690929
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing buprenorphine/naloxone and methadone for the treatment of patients with failed back surgery syndrome and opioid addiction

Abstract: Opioid analgesic consumption has led to an unprecedented epidemic of overdose death and opioid addiction in the US history. The treatment of chronic pain in patients with opioid addiction who receive prescriptions for opioid medications presents a clinical dilemma. Continuing opioid medication could result in hyperalgesia rendering opioids ineffective and in an iatrogenic therapeutic damage as evidenced by the worsening of addiction. Discontinuing opioid medications could result in severe pain and cravings tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(77 citation statements)
references
References 21 publications
3
73
1
Order By: Relevance
“…9,11 There is evidence that buprenorphine can provide analgesia for chronic pain 16 including sublingual buprenorphine/naloxone preparations approved for OUD treatment. 11,[17][18][19][20] However, conclusive evidence regarding the effectiveness and safety of sublingual buprenorphine/naloxone for CPOD and chronic pain awaits prospective randomized trials. These trials will also need to determine the effective buprenorphine dose, frequency of dosing, and treatment length for treating CPOD.…”
Section: Buprenorphine Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11 There is evidence that buprenorphine can provide analgesia for chronic pain 16 including sublingual buprenorphine/naloxone preparations approved for OUD treatment. 11,[17][18][19][20] However, conclusive evidence regarding the effectiveness and safety of sublingual buprenorphine/naloxone for CPOD and chronic pain awaits prospective randomized trials. These trials will also need to determine the effective buprenorphine dose, frequency of dosing, and treatment length for treating CPOD.…”
Section: Buprenorphine Treatmentmentioning
confidence: 99%
“…More detailed discussion regarding the current methods of buprenorphine utilization in CPOD is beyond the scope of this article and is provided elsewhere. 11,20 Methadone, an effective OUD treatment, has also been used in clinical situations suggestive of CPOD with reasonable effectiveness, 19,22 but the higher burden of dependence that may worsen pain and elevated opioid risk associated with methadone makes buprenorphine a more appealing choice. 11,19 There is little evidence or clinical experience with naltrexone, another medication used in OUD treatment, but its antagonism of the mu receptor suggests disutility in pain treatment.…”
Section: Buprenorphine Treatmentmentioning
confidence: 99%
“…An alternative strategy for these patients might be opioid agonist treatment (OAT) with a long-acting mu-opioid receptor agonist, since long-acting opioids might not only stabilize opioid use, but simultaneously provide pain relief. Indeed, some studies investigated the potential of methadone as an OAT in patients with prescription OUD and CNCP, showing long-lasting improvement in pain control [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that buprenorphine has similar equi-analgesic properties as full mu-opioid receptor agonists, like morphine and transdermal fentanyl [26]. Studies on the effectiveness of buprenorphine rotation in patients with CNCP and OUD suggested a positive effect on pain [23,[27][28][29][30][31]. However, these studies had a small sample size [23,31], were retrospective in nature [27,28,30], or participants could self-administer additional oxycodone [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation